A non-aqueous electrolyte and lithium ion battery
By using a specific proportion and content of nonaqueous electrolyte components in lithium-ion batteries, the problem of deterioration of performance and rapid growth of impedance at high temperatures is solved, and the battery's high-temperature fast charging cycle performance and safety is improved.
Patent Information
- Application Number
- CN202411864761.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The performance of existing lithium-ion battery electrolytes deteriorates at high temperatures and the impedance increases rapidly, affecting the cycle stability and safety of the battery.
A nonaqueous electrolyte is used, which consists of lithium hexafluorophosphate, a first additive (such as at least one of Compounds 1-3), difluorophosphate ions and tris(trimethylsilyl)phosphate esters. By adjusting the proportion and content of these components, it is ensured that the density and component relationship of the nonaqueous electrolyte meet a specific range to reduce the initial impedance and improve the high-temperature fast charging cycle performance.
It achieves excellent performance of lithium-ion batteries under high temperature conditions, reduces impedance growth, extends the cycle life of the battery, and improves safety.
Smart Images

Figure SMS_12 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a non-aqueous electrolyte and a lithium ion battery having excellent high temperature performance and relatively low impedance. Background Art
[0002] Lithium-ion batteries are now widely used in personal electronic products and electric vehicles. Lithium-ion batteries are mainly composed of four key parts: positive electrode, negative electrode, electrolyte and diaphragm. The stability of the electrolyte not only limits the battery potential window, but also the continuous decomposition of the electrolyte will cause a significant degradation of battery performance. Therefore, studying the chemical and electrochemical reactions of the electrolyte in the battery is an effective way to improve battery performance.
[0003] The most common electrolyte system at present is lithium hexafluorophosphate (LiPF6) dissolved in carbonate solvents. As the most commonly used lithium salt in lithium-ion batteries, LiPF6 has two major disadvantages: poor thermal stability and water sensitivity. In actual use, side reactions may occur to generate PF5, POF3, PF2O2 - , HF and other byproducts. The decomposition mechanism of LiPF6 is still controversial. It is generally believed that LiF generated by the decomposition of LiPF6 helps to form a highly stable SEI film, while the HF acid produced will destroy the positive and negative electrode materials and the interface film and thus deteriorate the high temperature performance of the battery. Tris(trimethylsilyl)phosphate (TMSP) is often used in fast-charging electrolyte formulations because it can usually reduce impedance; however, TMSP catalyzes the decomposition of LiPF6 and is accompanied by the generation of gas, which significantly increases the impact of lithium salt decomposition on battery performance. Therefore, the development of an electrolyte that can fully utilize the decomposition of lithium salts to form a LiF-rich interface film and reduce the negative impact of HF generated by the decomposition of lithium salts on the battery is of great significance for batteries that take into account both impedance and high temperature performance. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a non-aqueous electrolyte and a lithium-ion battery with excellent high-temperature performance and relatively low impedance.
[0005] The present invention adopts the following technical solutions:
[0006] A non-aqueous electrolyte comprising an organic solvent, a lithium salt, difluorophosphate ions, tris(trimethylsilyl)phosphate and a first additive;
[0007] The lithium salt includes lithium hexafluorophosphate;
[0008] The first additive includes at least one of Compound 1 to Compound 3:
[0009] Compound 1; Compound 2; Compound 3;
[0010] The non-aqueous electrolyte meets the following conditions:
[0011] 0.05≤a / b≤20, 0.03≤a / c≤15, 0.05≤c×d / b≤20, 0.01≤a≤1, 0.01≤b≤1.2, 0.01≤c≤0.8, 1.1≤d≤1.3;
[0012] Wherein, a is the mass percentage of the first additive in the non-aqueous electrolyte, in units of %;
[0013] b is the mass percentage of difluorophosphate ion in the non-aqueous electrolyte, unit is %;
[0014] c is the mass percentage of tris(trimethylsilyl)phosphate in the non-aqueous electrolyte, in %.
[0015] d is the density of the non-aqueous electrolyte, in g / ml.
[0016] The non-aqueous electrolyte of the present invention adopts lithium hexafluorophosphate as lithium salt, a first additive and tris(trimethylsilyl)phosphate as additives. The inventors have found through extensive research that when the relationship between the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of difluorophosphate ions, the mass percentage c of tris(trimethylsilyl)phosphate, and the density d of the non-aqueous electrolyte satisfies 0.05≤a / b≤20, 0.03≤a / c≤15, 0.05≤c×d / b≤20, 0.01≤a≤1, 0.01≤b≤1.2, 0.01≤c≤0.8, 1.1≤d≤1.3, both low initial impedance and excellent high-temperature fast-charge cycle performance can be taken into account, and the problem of rapid impedance growth during high-temperature fast-charge cycles can be suppressed. It is speculated that this is because tris(trimethylsilyl)phosphate, as an additive, can reduce impedance. On the one hand, it can participate in film formation to form an interface film component containing phosphorus elements, and on the other hand, it can react with lithium salts to produce The byproducts include lithium difluorophosphate and the like. The participation of lithium difluorophosphate in film formation will form an interface film rich in lithium fluoride components, thereby improving the battery impedance. However, the reaction of tri(trimethylsilyl)phosphate with lithium salt will produce certain side effects, mainly because the production of other products of lithium salt decomposition, such as HF, will cause serious deterioration of the quality of the electrolyte and the battery performance. Even if tri(trimethylsilyl)phosphate can react with water and HF to achieve the effect of removing water and acid, the reaction product is still acid or TMSF and the like. The produced acid may still attack the interface film and TMSF is a gas at room temperature, which will cause the pole piece to be not tightly attached and the lithium to be unevenly embedded. In order to solve the negative impact of tri(trimethylsilyl)phosphate, a first additive is further added, which is easier to combine with fluoride ions than tri(trimethylsilyl)phosphate, reduces the adverse products produced by the decomposition of tri(trimethylsilyl)phosphate and lithium salt, and significantly reduces the risk of deteriorating the high temperature performance of the battery when tri(trimethylsilyl)phosphate is used as an additive. The density change of the non-aqueous electrolyte reflects the change of the components or proportions of the non-aqueous electrolyte. The change of density will significantly affect the degree of reaction between tris(trimethylsilyl)phosphate and lithium salt, and thus affect the effect of the first additive on the reaction. When the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of difluorophosphate ions, the mass percentage c of tris(trimethylsilyl)phosphate, and the density d of the non-aqueous electrolyte are in a synergistic state, the battery can take into account both low initial impedance and excellent high-temperature fast-charge cycle performance, suppress the problem of rapid impedance growth during high-temperature fast-charge cycles, and give play to the positive effect of the electrolyte being easy to generate a LiF-rich interface film when tris(trimethylsilyl)phosphate is used as an additive, and suppress the negative effect of the accompanying generation of HF that affects the electrochemical performance of the battery.
[0017] When the relationship between the mass percentage a of the first additive in the non-aqueous electrolyte and the mass percentage b of the difluorophosphate ion is less than 0.05, it means that there is too little first additive or there are too many difluorophosphate ions in the electrolyte; if the a value is too small, it is difficult to decompose to form a highly stable, dense and uniform film and it is difficult to inhibit the negative effects of the reaction between tris(trimethylsilyl)phosphate and LiPF6; if the b value is too large, it is usually because too many difluorophosphate ion-containing compounds are added or LiPF6 is severely hydrolyzed, and the consequence is that it is easy to precipitate from the electrolyte in the form of LiPO2F2, resulting in uneven force between the pole pieces and uneven lithium deintercalation during the cycle process, which becomes a battery failure site. Although too much LiPO2F2 is easy to form an interface film rich in LiF, it also makes the proportion of inorganic matter in the membrane components too high, thereby affecting lithium ion transmission and causing the battery impedance to be too large.
[0018] When the relationship between the mass percentage a of the first additive in the non-aqueous electrolyte and the mass percentage b of the difluorophosphate ion is a / b>20, it means that there is too much first additive or there are too few difluorophosphate ions in the electrolyte; if the a value is too large, although a highly stable, dense and uniform film can be formed, the impedance of the positive and negative electrode membranes is too large, which aggravates the heat generation of the battery and the transmission kinetics of lithium ions in the interface film are poor, and the battery is prone to diving (extremely rapid capacity decay during the cycle) and has a high safety risk; if the b value is too small, it usually means that the degree of reaction between the trimethylsilyl group and LiPF6 is extremely low without the addition of a difluorophosphate ion-containing compound. Although the hydrolysis of LiPF6 is well controlled so that the HF acid content in the electrolyte is also low, it is impossible to use the LiPO2F2 product generated by the reaction of the trimethylsilyl group and LiPF6 to form a LiF-rich interface film to improve the battery impedance and high temperature performance.
[0019] Preferably, the relationship between the mass percentage a of the first additive and the mass percentage b of the difluorophosphate ion in the non-aqueous electrolyte satisfies 0.1≤a / b≤10.
[0020] When the relationship between the mass percentage a of the first additive and the mass percentage c of tri(trimethylsilyl) phosphate in the non-aqueous electrolyte is a / c<0.03, it means that the first additive is too little or the tri(trimethylsilyl) phosphate is too much; if the a value is too small, it is difficult to decompose to form a highly stable and dense and uniform film and it is difficult to inhibit the negative effects of the reaction between tri(trimethylsilyl) phosphate and LiPF6; if the c value is too large, it will cause the lithium salt to decompose and the acidity in the electrolyte to be too high. The acidity increases rapidly at high temperature and then destroys the positive and negative electrode interface film. More active lithium needs to be consumed in the cycle for film repair and aggravates the side reactions between the electrode and the electrolyte. In response, HF will also attack the active materials of the positive and negative electrodes, causing the dissolution of transition metal ions and the destruction of the electrode structure. Transition metal ions will also catalyze the decomposition of lithium salts and solvents to produce more HF and adverse by-products, forming a vicious circle, which is reflected at the battery level as rapid decay of cycle capacity and increase of impedance. In addition, the high content of tris(trimethylsilyl) phosphate reacts with LiPF6 at high temperature to generate LiPO2F2, which can even cause LiPO2F2 to precipitate, turning it into a solid impurity and causing battery performance to deteriorate. At the same time, a small amount of gas containing TMSF, CO2 and other components will be produced, which will cause the battery cell electrodes to not fit tightly and the battery to be sealed empty.
[0021] When the relationship between the mass percentage a of the first additive and the mass percentage c of tris(trimethylsilyl) phosphate in the non-aqueous electrolyte is a / c>15, it means that there is too much first additive or too little tris(trimethylsilyl) phosphate; if the a value is too large, although a highly stable, dense and uniform film can be formed, the impedance of the positive and negative electrode membranes is too large, which aggravates the heat generation of the battery and the transmission kinetics of lithium ions in the interface membrane are poor, and the battery is prone to diving (extremely rapid capacity decay during the cycle) and has a higher safety risk; if the c value is too small, the battery impedance cannot be effectively reduced, and it is difficult to meet the performance requirements of low impedance and high rate of the battery.
[0022] Preferably, the relationship between the mass percentage a of the first additive and the mass percentage c of tris(trimethylsilyl)phosphate in the non-aqueous electrolyte satisfies 0.1≤a / c≤10.
[0023] It is worth noting that the mass percentage b of difluorophosphate ions in the non-aqueous electrolyte will be affected by the mass percentage c of tris(trimethylsilyl) phosphate, but there is no necessary connection. Compounds containing difluorophosphate ions can also be added to directly regulate the size of the b value; at the same time, the reaction between tris(trimethylsilyl) phosphate and LiPF6 will also be affected by many factors, such as temperature, residual water in the electrolyte, product concentration and the chemical properties of other components in the electrolyte.
[0024] When the relationship between the mass percentage b of difluorophosphate ions, the mass percentage c of tris(trimethylsilyl)phosphate, and the density d of the non-aqueous electrolyte is c×d / b<0.05, it means that the content of difluorophosphate ions is too high or the content of tris(trimethylsilyl)phosphate is too low or the density of the non-aqueous electrolyte is too low. The former two will lead to degradation or failure of battery performance, while the non-aqueous electrolyte density d is too low, which means that the electrolyte has less lithium salt content or less cyclic carbonate components with higher density. Although insufficient lithium salt can also reduce the degree of its decomposition, it will significantly weaken the ability of the electrolyte to transport lithium ions. If the cyclic carbonate accounts for too little as a solvent component, the lithium salt cannot be fully dissociated. Although the possibility of lithium salt decomposition is also reduced, the undissociated lithium salt is difficult to migrate quickly as a macromolecule. Therefore, although the non-aqueous electrolyte density is too low to weaken the decomposition of lithium salt and its influence, the sacrifice of lithium ion migration kinetics is too great, and the battery impedance and other performances will be significantly reduced.
[0025] When the relationship between the mass percentage b of difluorophosphate ions, the mass percentage c of tris(trimethylsilyl)phosphate, and the density d of the non-aqueous electrolyte is c×d / b>20, it means that the content of difluorophosphate ions is too low or the content of tris(trimethylsilyl)phosphate is too high or the density of the non-aqueous electrolyte is too high. If the difluorophosphate ions are too low, the battery performance cannot be effectively improved. If the content of tris(trimethylsilyl)phosphate is too high, there will be too many side reactions with lithium salts and deteriorate the battery performance. If the density d of the non-aqueous electrolyte is too high, it means that the lithium salt content is too high or there are too many cyclic carbonates with higher density. If the lithium salt is too much, the decomposition will be more violent and the excess lithium salt cannot be dissociated and will hinder the migration of normal solvated lithium ions as a macromolecule. If the cyclic carbonate accounts for too much as a solvent component, the viscosity of the electrolyte will be significantly increased. The migration rate of lithium ions will be significantly affected under high viscosity. Therefore, if the density of the non-aqueous electrolyte is too high, it may aggravate the decomposition of lithium salts and deteriorate the kinetic performance, ultimately affecting all aspects of the battery performance.
[0026] Preferably, the relationship between the mass percentage b of difluorophosphate ions in the non-aqueous electrolyte, the mass percentage c of tris(trimethylsilyl)phosphate, and the density d of the non-aqueous electrolyte satisfies 0.1≤c×d / b≤5.
[0027] The first additive can participate in the formation of a dense and uniform interface film at both the positive and negative electrodes, improve the stability of the interface film and its tolerance to HF attack, thereby improving the high temperature performance of the battery. In addition, it also has a stronger affinity with free F than trimethylsilyl groups and protons H. -The ability to combine makes the different decomposition routes of lithium salts focus more on the reaction with tri(trimethylsilyl)phosphate to generate lithium difluorophosphate and inhibit the production of byproducts with significant negative effects such as HF and TMSF. If the a value is too high, the battery impedance is too large, and the battery charge and discharge polarization and heat generation increase significantly, causing a series of negative effects such as thermal decomposition of lithium salts and impedance growth, and ultimately deteriorating the various electrochemical properties of the battery; if the a value is too low, it is difficult to improve the high-temperature performance of the battery, and the tri(trimethylsilyl)phosphate in the electrolyte reacts with the lithium salt to deteriorate the performance, and the risk of gas production or impedance growth will increase significantly. Specifically, in some embodiments of the present invention, the mass percentage a% of the first additive in the non-aqueous electrolyte is 0.01%, 0.03%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range consisting of any two of these values; preferably, the mass percentage a% of the first additive in the non-aqueous electrolyte is 0.05~0.5%.
[0028] The first additive of the present invention has a tricyclic structure, which significantly weakens its ability to bind to fluoride ions compared to a bicyclic structure or a monocyclic structure, thereby failing to inhibit the degradation of battery performance by decomposition byproducts of lithium salts and trimethylsilyl groups.
[0029] In some preferred embodiments of the present invention, the first additive includes at least one of compound 1 and compound 2. Compared with compound 3, compound 1 and compound 2 have the ring structure of ethylene carbonate and ethylene sulfate at the same time, have a higher HOMO energy and a lower LUMO energy than the carbonate solvent, and thus can undergo redox polymerization reaction at the positive electrode and the negative electrode in priority to the solvent to form an interface film on the electrode surface. The formed interface film has good ionic conductivity, can improve the transmission rate of lithium ions, and then reduce the internal resistance of the battery, so that the battery has excellent high-temperature fast charging cycle performance.
[0030] The difluorophosphate ions in the non-aqueous electrolyte of the present invention come from the hydrolysis of the compound containing difluorophosphate ions and / or the lithium hexafluorophosphate of lithium salt. The content of difluorophosphate ions in the non-aqueous electrolyte can be regulated by controlling the amount of the compound containing difluorophosphate ions added to the electrolyte or the degree of hydrolysis of the lithium hexafluorophosphate of lithium salt. The specific regulation method is not limited by the present invention. As long as the content of difluorophosphate ions in the non-aqueous electrolyte meets the range defined by the present invention, it is within the concept of the present invention. Difluorophosphate ions can participate in the formation of SEI film, increase the content of LiF in the membrane component, and thus improve the stability of SEI film and reduce membrane impedance. If the b value is too high, it is easy to precipitate from the electrolyte in the form of lithium difluorophosphate or cannot be completely dissolved. As an impurity foreign body, it causes uneven force inside the battery and deteriorates the battery performance, and too high a content may cause too many inorganic components in the interface film and deteriorate the battery impedance; if the b value is too low, it is difficult to form an interface film rich in LiF, and the battery impedance and high temperature performance cannot be improved. Specifically, in some embodiments of the present invention, the mass percentage b% of difluorophosphate ions in the non-aqueous electrolyte is 0.01%, 0.03%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2% or a range consisting of any two of these values; preferably, the mass percentage b% of difluorophosphate ions in the non-aqueous electrolyte is 0.05-0.8%. More preferably, the mass percentage b% of difluorophosphate ions in the non-aqueous electrolyte is 0.1-0.4%.
[0031] In the non-aqueous electrolyte of the present invention, the mass percentage of difluorophosphate ions has the same meaning as the concentration of difluorophosphate ions; the method for determining the mass percentage of difluorophosphate ions is not particularly limited in the present invention, and a test method known in the art can be used, such as ion chromatography, 19 F NMR, etc.
[0032] Tris(trimethylsilyl)phosphate can promote the hydrolysis of LiPF6 to produce decomposition products such as LiPO2F2 and HF. The presence of LiPO2F2 component can participate in the formation of SEI film, increase the content of LiF in the film component, and thus improve the stability of SEI film and reduce film impedance. On the other hand, the generation of HF acid will attack the positive and negative electrode interface film and even corrode the electrode material, causing a series of negative effects, such as a significant increase in film impedance. Therefore, the content of tris(trimethylsilyl)phosphate is required to be relatively high. If the c value is too high, the decomposition degree of lithium salt in the electrolyte will be significantly aggravated, and the high acidity of the electrolyte will cause serious deterioration of battery performance; if the c value is too low, the improvement of battery impedance is very limited. Specifically, in some embodiments of the present invention, the mass percentage c% of tris(trimethylsilyl) phosphate in the non-aqueous electrolyte is 0.01%, 0.03%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8% or a range consisting of any two of these values; preferably, the mass percentage c% of tris(trimethylsilyl) phosphate in the non-aqueous electrolyte is 0.05~0.5%.
[0033] Specifically, in some embodiments of the present invention, the compound containing difluorophosphate ions includes lithium difluorophosphate.
[0034] Specifically, in some embodiments of the present invention, the lithium salt also includes lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), LiPO2F2, LiBF4, LiBOB, LiSbF6, LiAsF6, LiCF3SO3, LiDFOB, LiDFOP, LiN(SO2CF3)2, LiC(SO2CF3)3, LiN(SO2C2F5)2, LiCl, LiBr, LiI, LiClO4, LiB 10 Cl 10 , LiAlCl4, lithium chloroborane, lithium lower aliphatic carboxylate having 4 or less carbon atoms, and lithium tetraphenylborate.
[0035] Specifically, in some embodiments of the present invention, the organic solvent includes at least one of a cyclic carbonate solvent, a linear carbonate solvent, a carboxylate solvent, and an ether solvent.
[0036] In some preferred embodiments, the cyclic carbonate solvent includes at least one of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, vinylene carbonate and butylene carbonate.
[0037] In some preferred embodiments, the linear carbonate solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate.
[0038] In some preferred embodiments, the carboxylate solvent includes at least one of ethyl acetate, ethyl propionate, propyl propionate, ethyl difluoroacetate, methyl acetate, methyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate and ethyl trimethylacetate.
[0039] In some preferred embodiments, the ether solvent includes at least one of ethylene glycol dimethyl ether, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
[0040] Specifically, in some embodiments of the present invention, the density d of the non-aqueous electrolyte is 1.1~1.3g / mL. By regulating the density of the non-aqueous electrolyte within the above range, the degree of decomposition of lithium hexafluorophosphate can be reduced, the generation of HF acid can be reduced, and the battery can have good cycle performance. The density of the non-aqueous electrolyte is affected by the type and content of the solvent and the lithium salt. Too low a density of the electrolyte may be due to too low a lithium salt concentration or too low an organic solvent density; although too low a lithium salt concentration can weaken the reaction between the lithium salt and tris(trimethylsilyl)phosphate and the hydrolysis of the lithium salt, it also severely weakens the lithium ion migration ability of the electrolyte. Not only is it difficult to generate interfacial film components that are easily conductive to lithium, such as LiF and alkyl lithium carbonate, during film formation, it is also unable to play a bridging role between the positive and negative electrodes for the rapid passage of lithium ions during the battery cycle, ultimately resulting in the initialization of the battery. The impedance increases and the battery is prone to drop during fast charging cycles (the battery capacity decays rapidly within a short cycle number); the density of the organic solvent is too low, usually because too little high-density cyclic carbonate solvent is added. The cyclic carbonate in the solvent usually plays a role in dissociating lithium salts and forming a solvation structure with lithium ions. Too low a density will result in a low dielectric constant of the electrolyte, which cannot fully dissociate lithium salts. Although it inhibits lithium salt-related side reactions, it also severely weakens the lithium ion migration ability of the electrolyte, thereby causing battery performance degradation, that is, poor impedance and rate performance at the battery level. Excessive electrolyte density may be due to excessive lithium salt concentration or excessive organic solvent density. Excessive lithium salt is limited by the dissociation ability of the solvent and cannot improve the lithium ion migration ability of the electrolyte. Instead, it may hinder the normal solvated lithium ion migration as an undissociated component. In addition, excessive lithium salt will significantly aggravate the side reaction with tris(trimethylsilyl)phosphate and the hydrolysis reaction of the lithium salt itself, generating by-products such as HF that deteriorate battery performance. An organic solvent with too high a density usually means too many high-viscosity components. The increase in electrolyte viscosity will hinder the rapid migration of lithium ions, ultimately causing high battery impedance and poor rate performance.More specifically, the density of the non-aqueous electrolyte is 1.1 g / mL, 1.12 g / mL, 1.131 g / mL, 1.136 g / mL, 1.14 g / mL, 1.148 g / mL, 1.15 g / mL, 1.154 g / mL, 1.16 g / mL, 1.177 g / mL, 1.180 g / mL, 1.184 g / mL, 1.187 g / mL, 1.19 g / mL, 1.196 g / mL, 1.2 g / mL, 1.21 g / mL, 1.218 g / mL, 1.22 g / mL, 1.225 g / mL, 1.23 g / mL, 1.233 g / mL, 1.24 g / mL, 1.246 g / mL, 1.25 g / mL, 1.256 g / mL, 1.26 g / mL, 1.264 g / mL, 1.27 g / mL, 1.275 g / mL, 1.28 g / mL, 1.286 g / mL, 1.291 g / mL, 1.296 g / mL, 1.3 g / mL or a range consisting of any two of these values; preferably, the density of the nonaqueous electrolyte is 1.14-1.26 g / mL. More preferably, the density of the nonaqueous electrolyte is 1.14-1.22 g / mL.
[0041] Specifically, in some embodiments of the present invention, the non-aqueous electrolyte further includes an auxiliary additive, and the auxiliary additive includes at least one of cyclic sulfate compounds, sultone compounds, cyclic carbonate compounds, phosphate compounds, borate compounds and nitrile compounds.
[0042] In some preferred embodiments, the cyclic sulfate ester compound includes at least one of 4-methylvinyl sulfate, vinyl sulfate, and propylene sulfate.
[0043] In some preferred embodiments, the sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, and propenyl-1,3-sultone.
[0044] In some preferred embodiments, the cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 1:
[0045] Structural formula 1;
[0046] In the structural formula 1 shown, R 21 , R 22 , R 23 , R 24 , R 25 , R 26Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group;
[0047] In some preferred embodiments, the compound represented by structural formula 1 includes at least one of the compounds represented by compounds 1-1 to 1-6 below:
[0048] Compound 1-1; Compound 1-2; Compound 1-3
[0049] Compounds 1-4; Compounds 1-5; Compounds 1-6;
[0050] In some preferred embodiments, the phosphate compound includes at least one of the compounds shown in the following structural formula 2:
[0051] Structural formula 2;
[0052] In the structural formula 2, R 31 , R 32 , R 33 Each independently selected from a saturated hydrocarbon group, an unsaturated hydrocarbon group, and a halogenated hydrocarbon group of C1-C5; more preferably, the compound shown in structural formula 2 includes at least one of tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, and diallyl hexafluoroisopropyl phosphate.
[0053] In some preferred embodiments, the borate ester compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate.
[0054] In some preferred embodiments, the nitrile compound includes at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.
[0055] In some embodiments, based on the total mass of the non-aqueous electrolyte as 100%, the content of the auxiliary additive is 0.01% to 10%. Preferably, the content is 0.1% to 5%; more preferably, the content is 0.1% to 2%. Specifically, the content of any one of the optional substances in the auxiliary additive can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5% or a range consisting of any two of these values.
[0056] In a second aspect, the present invention further provides a lithium-ion battery comprising a positive electrode, a negative electrode and the above-mentioned non-aqueous electrolyte.
[0057] The negative electrode includes a negative electrode material layer containing a negative electrode active material. Specifically, in some embodiments of the present invention, the negative electrode material is any one or more of a silicon-based material and a carbon material. The silicon-based material is selected from one or more of a silicon material, a silicon oxide material, a silicon-carbon material and a silicon alloy material; preferably, the silicon material is a nano-silicon material; preferably, the silicon oxide material is a SiOx material, wherein 0≤x<2; preferably, the silicon-carbon material is: a silicon-based material containing silicon and carbon materials, and / or a silicon-based material containing SiOy and carbon materials, wherein 0≤y<2; preferably, the silicon alloy material is a Mg2Si alloy material and / or a Fe2Si alloy material. The carbon material is selected from one or more of artificial graphite, natural graphite, composite graphite, graphene, and hard carbon; preferably, the carbon material is an artificial graphite material.
[0058] Specifically, in some embodiments of the present invention, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductor.
[0059] The negative electrode binder includes polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of vinylidene fluoride-tetrafluoroethylene, copolymers of vinylidene fluoride-trifluoroethylene, copolymers of vinylidene fluoride-trichloroethylene, copolymers of vinylidene fluoride-fluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, thermoplastic resins such as polyethylene and polypropylene; acrylic resin; and one or more of styrene butadiene rubber.
[0060] The negative electrode conductive agent includes one or more of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0061] Specifically, in some embodiments of the present invention, the negative electrode further comprises a negative electrode current collector, and the negative electrode material layer is disposed on the surface of the negative electrode current collector. The negative electrode current collector comprises a metal material that can conduct electrons, and preferably, the negative electrode current collector comprises one or more of aluminum, nickel, tin, copper, and stainless steel.
[0062] Specifically, in some embodiments of the present invention, the positive electrode includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material may include LiFe 1-x’ M' x’ PO4、LiMn 2-y’ M y’ O4 and LiNi x Co y Mn z M 1-x-y-z O2, wherein M' is selected from one or more of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, M is selected from one or more of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and 0≤x'<1, 0≤y'≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1, the positive electrode active material may also include one or more of sulfide, selenide, and halide. More preferably, the positive electrode active material may include LiCoO2, LiFePO4, LiFe 0.4 Mn 0.6 PO4, LiMn2O4, LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.5 Co 0.2 Mn 0.2 Al 0.1 O2、LiNi 0.5 Co 0.2 Al 0.3One or more of O2.
[0063] Specifically, in some embodiments of the present invention, the positive electrode further comprises a positive electrode current collector, and the positive electrode material layer is disposed on the surface of the positive electrode current collector. The material of the positive electrode current collector may be the same as that of the positive electrode current collector, which will not be described in detail herein.
[0064] Specifically, in some embodiments of the present invention, the positive electrode material layer further includes a positive electrode binder and a positive electrode conductor, and the positive electrode active material, the positive electrode binder and the positive electrode conductor are blended to obtain the positive electrode material layer. The positive electrode binder and the positive electrode conductor may be the same as the negative electrode binder and the negative electrode conductor, respectively, and will not be described in detail here.
[0065] Specifically, in some embodiments of the present invention, the lithium-ion battery further includes a diaphragm, and the diaphragm is located between the positive electrode and the negative electrode.
[0066] The diaphragm may be an existing conventional diaphragm, such as a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an inorganic-organic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.
[0067] The non-aqueous electrolyte of the present invention uses a first additive and tris(trimethylsilyl)phosphate as additives, and limits the relationship between the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of difluorophosphate ions, the mass percentage c of tris(trimethylsilyl)phosphate, and the density d of the non-aqueous electrolyte to satisfy 0.05≤a / b≤20, 0.03≤a / c≤15, 0.05≤c×d / b≤20, 0.01≤a≤1, 0.01≤b≤1.2, 0.01≤c≤0.8, and 1.1≤d≤1.3. The advantages of tris(trimethylsilyl)phosphate in reducing battery impedance and forming a highly stable LiF-rich interface film can be fully utilized, while the disadvantage of catalyzing the decomposition of lithium salts to produce adverse byproducts is greatly suppressed. At the battery level, both low initial impedance and excellent high-temperature fast charging cycle performance can be taken into account, and the problem of rapid impedance growth during high-temperature fast charging cycles can be suppressed. DETAILED DESCRIPTION
[0068] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0069] In the examples and comparative examples of the present invention, one of the compounds shown in Table 1 is used as a non-aqueous electrolyte additive.
[0070] Table 1
[0071]
[0072] Example 1
[0073] The method for preparing a lithium-ion battery in this embodiment comprises the following steps:
[0074] 1) Preparation of positive electrode sheet:
[0075] LiNi 0.5 Mn 0.3 Co 0.2 O2, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 97:1.5:1.5, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil, and after drying, rolling and vacuum drying, the positive electrode material layer is obtained, and the aluminum lead wire is welded with an ultrasonic welder to obtain the positive electrode sheet.
[0076] 2) Preparation of negative electrode sheet:
[0077] The negative electrode active material graphite, conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) were mixed in a mass ratio of 96.3:1.0:1.2:1.5, and then dispersed in deionized water to obtain a negative electrode slurry. The slurry was coated on both sides of the copper foil, dried, rolled and vacuum dried, and the nickel lead wire was welded with an ultrasonic welder to obtain a negative electrode sheet.
[0078] 3) Preparation of electrolyte:
[0079] Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a certain mass ratio, additives are added, and then lithium hexafluorophosphate (LiPF6) is added and its content is controlled so that the density of the non-aqueous electrolyte meets the set range. The density of each additive and the non-aqueous electrolyte is shown in Table 2.
[0080] 4) Preparation of diaphragm:
[0081] A three-layer isolation film of polypropylene, polyethylene and polypropylene is used with a thickness of 20μm.
[0082] 5) Battery Assembly:
[0083] The prepared positive electrode sheet and the negative electrode sheet are assembled into a laminated soft-pack battery cell.
[0084] 6) Battery filling and formation
[0085] In a glove box with a dew point controlled below -40°C, the prepared electrolyte was injected into the battery cell, vacuum packaged, and left to stand for 72 hours. Then, the conventional formation of the first charge was carried out according to the following steps: 0.05C constant current charging for 180 minutes, 0.1C constant current charging for 120 minutes, 0.2C constant current charging for 120 minutes, secondary vacuum sealing, and then further full charging at a current of 0.2C (100% SOC), after being placed at room temperature for 72 hours, full discharge at a current of 0.2C (0% SOC).
[0086] Examples 2-28 and Comparative Examples 1-31
[0087] This embodiment and comparative example are used to compare and illustrate the lithium ion battery disclosed in the present invention, including most of the operating steps in the above-mentioned embodiment 1, and the difference lies in: the composition and content of the solvent, lithium salt and additive in the non-aqueous electrolyte, the concentration of the lithium salt and the composition of the solvent are not shown, and need to be adjusted according to actual conditions so that the density of the electrolyte meets the set range. The type and content of the additive and the density of the non-aqueous electrolyte are shown in Table 2.
[0088] Table 2
[0089] Group Cathode active material type The first additive type First additive content (%) Difluorophosphate ion content b (%) Tris(trimethylsilyl) phosphate content c(%) Density of non-aqueous electrolyte d(g / ml) Auxiliary additives and content (%) a / b a / c c×d / b Example 1 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.5 0.3 0.3 1.196 VC: 2 1.67 1.67 1.20 Example 2 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.3 0.1 0.1 1.177 VC: 2 3.00 3.00 1.18 Example 3 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.1 0.5 0.5 1.205 VC: 2 0.20 0.20 1.21 Example 4 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.05 0.8 0.8 1.286 VC: 2 0.06 0.06 1.29 Example 5 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.03 0.6 0.7 1.242 VC: 2 0.05 0.04 1.45 Example 6 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.01 0.03 0.3 1.279 VC: 2 0.33 0.03 12.79 Example 7 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.8 0.05 0.08 1.163 VC: 2 16.0 10.00 1.86 Example 8 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.2 0.01 0.05 1.151 VC: 2 20.0 4.00 5.76 Example 9 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.1 0.01 0.01 1.120 VC: 2 10.0 10.00 1.12 Example 10 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.08 0.4 0.06 1.195 VC: 2 0.20 1.33 0.18 Embodiment 11 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 1 0.9 0.6 1.252 VC: 2 1.11 1.67 0.83 Example 12 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.3 0.08 0.02 1.136 VC: 2 3.75 15.00 0.28 Embodiment 13 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.07 1.2 0.7 1.266 VC: 2 0.06 0.10 0.74 Embodiment 14 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.05 0.7 0.5 1.211 VC: 2 0.07 0.10 0.87 Embodiment 15 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.2 0.7 0.06 1.260 VC: 2 0.29 3.33 0.11 Example 16 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.1 0.04 0.7 1.135 VC: 2 2.50 0.14 19.86 Embodiment 17 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.1 0.3 0.2 1.187 VC: 2 0.33 0.50 0.79 Embodiment 18 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.5 0.3 0.3 1.114 VC: 2 1.67 1.67 1.11 Embodiment 19 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.5 0.3 0.3 1.298 VC: 2 1.67 1.67 1.30 Embodiment 20 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 2 0.5 0.3 0.3 1.196 VC: 2 1.67 1.67 1.20 Embodiment 21 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 3 0.5 0.3 0.3 1.196 VC: 2 1.67 1.67 1.20
[0090] Table 2
[0091] Embodiment 22 <![CDATA[LiMn 0.6 Fe 0.4 PO4]]> Compound 1 0.6 0.05 0.05 1.145 VC: 2 12.0 12.00 1.15 Embodiment 23 <![CDATA[LiNi 0.8 Mn 0.1 What 0.1 O2]]> Compound 1 0.02 0.2 0.3 1.189 VC: 2 0.10 0.07 1.78 Embodiment 24 <![CDATA[LiFePO4]]> Compound 1 0.4 0.7 0.5 1.122 VC: 2 0.57 0.80 0.80 Embodiment 25 <![CDATA[LiCoO2]]> Compound 1 0.2 0.4 0.2 1.184 VC: 2 0.50 1.00 0.59 Embodiment 26 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.5 0.3 0.3 1.191 / 1.67 1.67 1.19 Embodiment 27 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.5 0.3 0.3 1.193 VC: 1 1.67 1.67 1.19 Embodiment 28 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.5 0.3 0.3 1.198 VC: 3 1.67 1.67 1.20 Comparative Example 1 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0 0.3 0.3 1.190 VC: 2 0.00 0.00 1.19 Comparative Example 2 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0 0.3 0.3 1.183 / 0.00 0.00 1.18 Comparative Example 3 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0 0.3 0.3 1.185 VC: 1 0.00 0.00 1.19 Comparative Example 4 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0 0.3 0.3 1.192 VC: 3 0.00 0.00 1.19 Comparative Example 5 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.3 0.005 0.003 1.104 VC: 2 60.0 100 0.66 Comparative Example 6 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 2 0.5 0.5 1.236 VC: 2 4.00 4.00 1.24 Comparative Example 7 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 1.1 1 0.7 1.174 VC: 2 1.10 1.57 0.82 Comparative Example 8 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.008 0.08 0.05 1.154 VC: 2 0.10 0.16 0.72 Comparative Example 9 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.05 0.008 0.1 1.157 VC: 2 6.25 0.50 14.46 Comparative Example 10 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.5 1.3 0.3 1.192 VC: 2 0.38 1.67 0.28 Comparative Example 11 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.05 0.1 0.008 1.252 VC: 2 0.50 6.25 0.10 Comparative Example 12 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.5 0.5 1 1.189 VC: 2 1.00 0.50 2.38 Comparative Example 13 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.05 1.2 0.5 1.196 VC: 2 0.04 0.10 0.50 Comparative Example 14 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.85 0.04 0.4 1.195 VC: 2 21.25 2.13 11.95 Comparative Example 15 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.02 0.04 0.7 1.127 VC: 2 0.50 0.029 19.72 Comparative Example 16 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.8 0.08 0.05 1.198 VC: 2 10.00 16.0 0.75 Comparative Example 17 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.5 0.3 0.3 1.044 VC: 2 1.67 1.67 1.04
[0092] Table 2
[0093] Comparative Example 18 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.5 0.3 0.3 1.392 VC: 2 1.67 1.67 1.39 Comparative Example 19 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.4 0.04 0.7 1.272 VC: 2 10.00 0.57 22.26 Comparative Example 20 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.3 0.7 0.02 1.114 VC: 2 0.43 15.0 0.03 Comparative Example 21 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 1 1.5 2 1.295 VC: 2 0.67 0.50 1.73 Comparative Example 22 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.5 0.3 3 1.312 VC: 2 1.67 0.17 13.12 Comparative Example 23 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.8 0.02 0.06 1.168 VC: 2 40.00 13.33 3.50 Comparative Example 24 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.5 0.3 0.3 1.424 VC: 2 1.67 1.67 1.42 Comparative Example 25 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 1 0.5 0.3 0.3 1.055 VC: 2 1.67 1.67 1.06 Comparative Example 26 <![CDATA[LiMn 0.6 Fe 0.4 PO4]]> Compound 1 1.5 1.3 1 1.359 VC: 2 1.15 1.50 1.05 Comparative Example 27 <![CDATA[LiNi 0.8 Mn 0.1 What 0.1 O2]]> Compound 1 0.006 0.4 0.7 1.231 VC: 2 0.02 0.01 2.15 Comparative Example 28 <![CDATA[LiCoO2]]> Compound 1 0.5 1 0.03 1.147 VC: 2 0.50 16.67 0.03 Comparative Example 29 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 4 0.5 0.3 0.3 1.196 VC: 2 1.67 1.67 1.20 Comparative Example 30 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 5 0.5 0.3 0.3 1.196 VC: 2 1.67 1.67 1.20 Comparative Example 31 <![CDATA[LiNi 0.5 Mn 0.3 What 0.2 O2]]> Compound 6 0.5 0.3 0.3 1.196 VC: 2 1.67 1.67 1.20
[0094] The lithium ion batteries prepared in the examples and comparative examples were subjected to performance tests as follows:
[0095] 1. Battery initial and cycle 0℃ DCIR test
[0096] At room temperature (25°C), the battery was fully charged and discharged at a rate of 1C within the charge and discharge cut-off voltage commonly used in the corresponding system for 3 weeks, and the discharge capacity in the third week was taken as the capacity of the battery at the current 100% SOC.
[0097] At room temperature (25°C), the empty battery is charged with constant current to 50% of the battery's current capacity, and then the temperature is adjusted to 0°C and maintained for 6 hours.
[0098] 0.1C constant current charging for 10s and then resting for 40s; 0.1C constant current discharging for 10s and then resting for 40s, record the end voltage V1;
[0099] 0.2C constant current charging for 10s and then resting for 40s; 0.2C constant current discharging for 10s and then resting for 40s, record the end voltage V2;
[0100] 0.5C constant current charging for 10s and then resting for 40s; 0.5C constant current discharging for 10s and then resting for 40s, record the end voltage V3;
[0101] Draw a straight line with current as the horizontal axis and voltage as the vertical axis. The slope of the straight line is the 0℃ impedance.
[0102] The battery was tested in its initial state and at 0°C DCIR after 800 cycles.
[0103] 2. High temperature fast charging cycle performance test
[0104] At 45°C, the lithium ion batteries prepared in the examples and comparative examples were charged at a constant current and constant voltage of 3C (cut-off current 0.05C), and discharged at a rate of 3C, and fully charged and discharged within the charge and discharge cut-off voltage commonly used in the corresponding system (for example, 2.5-3.65V for lithium iron phosphate / artificial graphite system, and 3-4.25V for conventional ternary / artificial graphite system) The cycle test was performed until the capacity of the lithium ion battery decayed to 80% of the initial capacity, and the number of cycles was recorded.
[0105] (1) The test results of Examples 1-19 and Comparative Examples 5-25 are shown in Table 3.
[0106] Table 3
[0107] Group Battery initial 0℃ DCIR (mΩ) 0℃ DCIR (mΩ) after 800 cycles of battery 45℃ 3C / 3C cycle number to 80% capacity retention Example 1 217 241 1285 Example 2 224 249 1272 Example 3 219 245 1263 Example 4 264 326 1243 Example 5 258 315 1238 Example 6 243 337 1232 Example 7 247 296 1264 Example 8 241 287 1258 Example 9 245 272 1253 Example 10 226 244 1271 Embodiment 11 242 284 1250 Example 12 248 279 1256 Embodiment 13 266 343 1244 Embodiment 14 233 273 1278 Embodiment 15 241 278 1261 Example 16 249 334 1251 Embodiment 17 213 242 1275 Embodiment 18 233 268 1269 Embodiment 19 242 301 1245 Comparative Example 5 298 347 1120 Comparative Example 6 288 315 1125 Comparative Example 7 294 339 1117 Comparative Example 8 268 361 1111 Comparative Example 9 266 320 1104 Comparative Example 10 247 408 1021 Comparative Example 11 245 259 1127 Comparative Example 12 246 485 1100 Comparative Example 13 263 386 1039 Comparative Example 14 262 459 1129 Comparative Example 15 292 563 1088 Comparative Example 16 266 289 1134 Comparative Example 17 269 280 1109 Comparative Example 18 312 592 1021 Comparative Example 19 271 477 1104 Comparative Example 20 280 358 1095 Comparative Example 21 294 528 1082 Comparative Example 22 341 643 1011 Comparative Example 23 277 347 1132 Comparative Example 24 285 610 808 Comparative Example 25 297 385 883
[0108] It can be seen from the test results in Table 3 that the non-aqueous electrolyte of the present invention uses lithium hexafluorophosphate as the lithium salt, the first additive and tris(trimethylsilyl)phosphate as additives, and further controls the relationship between the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of the difluorophosphate ion, the mass percentage c of tris(trimethylsilyl)phosphate, and the density d of the non-aqueous electrolyte to satisfy 0.05≤a / b≤20, 0.03≤a / c≤15, 0.05≤c×d / b≤20, 0.01≤a≤1, 0.01≤b≤1.2, 0.01≤c≤0.8, and 1.1≤d≤1.3. The lithium ion battery using the above non-aqueous electrolyte can take into account both low initial impedance and excellent high-temperature fast charging cycle performance, and suppress the problem of rapid impedance growth during high-temperature fast charging cycles.
[0109] It can be seen from the test results of Example 1 and Comparative Examples 5-25 that when any one or more of the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of difluorophosphate ions, the mass percentage c of tris(trimethylsilyl) phosphate, and the density d of the non-aqueous electrolyte do not meet the specified range, or any one or more of the relationships a / b, a / c, c×d / b are too large or too small, the low impedance and high temperature fast charging cycle performance of the lithium ion battery cannot be taken into account; this indicates that the mass percentage a of the first additive, the mass percentage b of difluorophosphate ions, the mass percentage c of tris(trimethylsilyl) phosphate, and the density d of the non-aqueous electrolyte have a strong correlation in reducing the impedance of the lithium ion battery and optimizing the high temperature performance of the lithium ion battery.
[0110] (2) The test results of Example 1, Examples 20-21, and Comparative Examples 29-31 are shown in Table 4.
[0111] Table 4
[0112] Group Battery initial 0℃ DCIR (mΩ) 0℃ DCIR (mΩ) after 800 cycles of battery 45℃ 3C / 3C cycle number to 80% capacity retention Example 1 217 241 1285 Embodiment 20 213 255 1271 Embodiment 21 233 269 1219 Comparative Example 29 230 411 1101 Comparative Example 30 235 437 1111 Comparative Example 31 242 440 1093
[0113] It can be seen from the test results of Example 1 and Examples 20-21 in Table 4 that for the non-aqueous electrolyte of the present invention, when different first additives are used, when the mass percentage a of the first additive, the mass percentage b of difluorophosphate ions, the mass percentage c of tris(trimethylsilyl)phosphate, and the density d of the non-aqueous electrolyte meet the corresponding conditions, the impedance performance and high-temperature fast charging cycle performance of the lithium-ion battery can be optimized; this shows that the battery system of the present invention is universal for different first additives.
[0114] It can be seen from the test results of Example 1 and Comparative Examples 29-31 that when a single-ring or bicyclic compound is used, the degradation effect of the decomposition byproducts of lithium salts and tri(trimethylsilyl) phosphate on the battery performance cannot be suppressed, and the battery impedance and high-temperature fast-charging cycle performance cannot be improved, further illustrating the synergistic effect between the first additive and the other additives.
[0115] (3) The test results of Example 1, Examples 22-25, and Comparative Examples 26-28 are shown in Table 5.
[0116] Table 5
[0117] Group Battery initial 0℃ DCIR (mΩ) 0℃ DCIR (mΩ) after 800 cycles of battery 45℃ 3C / 3C cycle number to 80% capacity retention Example 1 217 241 1285 Embodiment 22 343 484 1145 Embodiment 23 203 236 1265 Embodiment 24 265 279 1497 Embodiment 25 199 247 1215 Comparative Example 26 474 987 886 Comparative Example 27 231 386 1095 Comparative Example 28 227 342 1073
[0118] It can be seen from the test results of Example 1, Examples 22-25 and Comparative Examples 26-28 in Table 5 that for the lithium ion battery of the present invention, when different positive electrode active materials are used, when the mass percentage a of the first additive, the mass percentage b of the difluorophosphate ion, the mass percentage c of tris(trimethylsilyl)phosphate, and the density d of the non-aqueous electrolyte meet the corresponding conditions, the impedance performance and high temperature performance of the lithium ion battery can be optimized; under the same positive electrode active material, when any of the mass percentage a of the first additive, the mass percentage b of the difluorophosphate ion, the mass percentage c of tris(trimethylsilyl)phosphate, and the density d of the non-aqueous electrolyte do not meet the corresponding conditions, the battery performance will be affected; indicating that the battery system of the present invention is universal for different positive electrode active materials.
[0119] (4) The test results of Example 1, Examples 26-28, and Comparative Examples 1-4 are shown in Table 6.
[0120] Table 6
[0121] Group Battery initial 0℃ DCIR (mΩ) 0℃ DCIR (mΩ) after 800 cycles of battery 45℃ 3C / 3C cycle number to 80% capacity retention Example 1 217 241 1285 Embodiment 26 196 243 1201 Embodiment 27 205 238 1254 Embodiment 28 228 256 1295 Comparative Example 1 259 396 1097 Comparative Example 2 252 512 952 Comparative Example 3 233 382 1012 Comparative Example 4 264 423 1069
[0122] From the test results of Example 1 and Examples 26-28 in Table 6, it can be seen that the lithium ion battery of the present invention, when used in combination with the auxiliary additive in the non-aqueous electrolyte, still has a good improvement effect on the impedance performance and high temperature performance of the lithium ion battery. From the test results of Example 1, Examples 26-28 and Comparative Examples 1-4, it can be seen that when different amounts of auxiliary additives are used to replace the first additive, the remaining additives cannot form a good synergistic effect, and the inhibition of the impedance growth of the lithium ion battery and the improvement of the high temperature cycle performance are not good.
[0123] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.
Claims
1. A non-aqueous electrolyte, characterized in that: The non-aqueous electrolyte comprises an organic solvent, a lithium salt, difluorophosphate ions, tris(trimethylsilyl)phosphate and a first additive; The lithium salt includes lithium hexafluorophosphate; The first additive includes at least one of Compound 1 to Compound 3: Compound 1 Compound 2 Compound 3 The non-aqueous electrolyte meets the following conditions: 0.05≤a / b≤20, 0.03≤a / c≤15, 0.05≤c×d / b≤20, 0.01≤a≤1, 0.01≤b≤1.2, 0.2≤c≤0.8, 1.1≤d≤1.3; Wherein, a is the mass percentage of the first additive in the non-aqueous electrolyte, in units of %; b is the mass percentage of difluorophosphate ion in the non-aqueous electrolyte, unit is %; c is the mass percentage of tris(trimethylsilyl)phosphate in the non-aqueous electrolyte, unit is %; d is the density of the non-aqueous electrolyte, in g / ml.
2. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte satisfies the following conditions: 0.1≤a / b≤10, 0.1≤a / c≤10, 0.1≤c×d / b≤5.
3. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage a% of the first additive in the non-aqueous electrolyte is 0.05%-0.5%.
4. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage b% of difluorophosphate ions in the non-aqueous electrolyte is 0.05%-0.8%.
5. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage c% of tri(trimethylsilyl)phosphate in the non-aqueous electrolyte is 0.2%-0.5%.
6. The non-aqueous electrolyte according to claim 1, characterized in that The density d of the non-aqueous electrolyte is 1.14 g / mL to 1.26 g / mL.
7. The non-aqueous electrolyte according to claim 6, characterized in that The density d of the non-aqueous electrolyte is 1.14 g / mL to 1.22 g / mL.
8. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte further includes an auxiliary additive, wherein the auxiliary additive includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a borate compound and a nitrile compound; and / or, Based on the total mass of the non-aqueous electrolyte as 100%, the content of the auxiliary additive is 0.01% to 10%; and / or, The cyclic sulfate ester compound includes at least one of 4-methylvinyl sulfate, vinyl sulfate, and propylene sulfate; and / or, The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone and propenyl-1,3-sultone; and / or, The cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 1: Structural formula 1 In the structural formula 1 shown, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or, The phosphate compound includes at least one of the compounds shown in the following structural formula 2: Structural formula 2 In the structural formula 2, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group; and / or, The borate compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate; and / or, The nitrile compound includes at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile.
9. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the non-aqueous electrolyte according to any one of claims 1 to 8.
10. The lithium ion battery according to claim 9, characterized in that: The positive electrode comprises a positive electrode material layer comprising a positive electrode active material, wherein the positive electrode active material comprises LiFe 1-x’ M' x’ PO4、LiMn 2-y’ M y’ O4 and LiNi x Co y Mn z M 1-x-y-z O2, wherein M' is selected from one or more of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, M is selected from one or more of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and 0≤x'<1, 0≤y'≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1.
Citation Information
Patent Citations
Lithium ion battery
CN115189029A
Cited By
Lithium ion battery and electrolyte thereof
CN120933479A